Carbon emission reduction mechanism of the pharmaceutical supply chain: Quadrilateral evolutionary game models - Zhao, Kai; Yang, Zheng-Fan; Zhuo, Yue; Zhang, Shan (Frontiers in Environmental Science, 2023)
The climate crisis and the increasing temperature of the earth have highlighted, the need to reduce carbon emissions in supply chains has gradually become a global consensus. The focus has often been on traditional carbon emission industries, such as energy and transportation, while the pharmaceutical industry has received little attention. This paper, therefore, aims to fill that research gap by exploring the carbon emission reduction mechanisms of the pharmaceutical supply chain, specifically the role of public participation. We constructed a quadrilateral evolutionary game model, based on evolutionary game theory, consisting of local government, pharmaceutical manufacturers, wastewater treatment plants and the public. By finding the equilibrium point of the system of replicator dynamics, evolutionary stable strategies are obtained. Our numerical simulation shows the impacts of the principal strategy change and the key variables. This paper also identifies some management implications: i) When local governments implement a combination policy (carbon subsidies and carbon tax policy), the key is to formulate a subsidy level satisfactory to the four parties. If the subsidy level is in the middle level, the four parties are at their most willing to participate in carbon emission reduction. ii) When local governments implement a single policy (carbon tax policy), the carbon tax rate becomes the key variable. A high level of carbon tax accelerates carbon emission reduction in the pharmaceutical supply chain. iii) No matter what policies local governments implement, the free-rider effect between pharmaceutical manufacturers and wastewater treatment plants always hinders their low-carbon decisions. iv) Public reporting is an effective measure for promoting carbon emission reduction in the pharmaceutical supply chain. When local governments implement a combination policy, it can reduce the cost of reporting and improve the willingness of the public to report. Finally, we put forward suggestions for rationalizing carbon emission reduction.